2019
DOI: 10.3389/fpsyg.2019.00416
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Experiences, Perceived Discrimination, and Psychological Distress Among Members of Various Socially Marginalized Groups

Abstract: Perceived discrimination has consistently been shown to be associated with diminished mental health, but the psychological processes underlying this link are less well understood. The present series of four studies assessed the role of a history traumatic events in generating a proliferation of discrimination stressors and threat appraisals, which in turn predict psychological distress (depressive and posttraumatic stress symptoms) (mediation model), or whether prior traumatic events sensitize group members, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 72 publications
4
35
0
Order By: Relevance
“…The current study demonstrated a robust association between discrimination and depressive symptoms in urban AI/AN, as has been shown by others (Gonzales et al, 2016;Kading et al, 2015;Matheson et al, 2019;Tucker et al, 2016;Whitbeck et al, 2002). More importantly, we found that this association varied by age and was significantly stronger for younger than older AI/AN adults.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current study demonstrated a robust association between discrimination and depressive symptoms in urban AI/AN, as has been shown by others (Gonzales et al, 2016;Kading et al, 2015;Matheson et al, 2019;Tucker et al, 2016;Whitbeck et al, 2002). More importantly, we found that this association varied by age and was significantly stronger for younger than older AI/AN adults.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with theoretical models of the adverse health effects of racial discrimination (Brondolo et al, 2018;Williams & Mohammed, 2013), research shows a robust link between reports of perceived racial discrimination and depression or depressive symptoms in AI/AN (Gonzales et al, 2016;Kading et al, 2015;Matheson et al, 2019;Tucker et al, 2016;Whitbeck et al, 2002), as found in other racialized and stigmatized groups (de Freitas et al, 2018;Paradies et al, 2015;Schmitt et al, 2014). Less clear, however, is whether this association varies over the life course.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Similar to findings from research on microaggressions (Sue et al, 2007), the uncertainty and ambiguity associated with everyday experiences of discrimination may, over time, exacerbate the negative psychological impact of growing up in adverse environments. Additionally, individuals with experiences of complex and continuous trauma may have an increased sensitivity toward perception of discrimination (Matheson et al, 2019). It could be that individuals with prior trauma have lower tolerance to everyday stressors and perceive more social rejection and exclusion (Todorova et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that instruments for measuring discrimination are grounded in subjective experiences, as victims are not always able to determine the true motivations behind an attack and as a result these tools are measuring perceived discrimination (Williams, 2016). Although the true motivations behind an incident may be unknown, the impact of an encounter perceived as discriminatory has the potential to inflict psychological distress and contribute to adverse health outcomes (Matheson et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%